Cluster policy as a development strategy: Case studies from the Middle East and North Africa - Maximilian Benner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
Cluster policy has become a method of choice for policymakers in many countries. Promoting strong localized industries is an appealing perspective for practitioners, as it can be seen as a way to anchor economic activity in regions in an era of globalization. If cluster policy is successful, it can contribute to the creation of employment and to the initiation of growth processes in urban regions and even in some rural ones. This makes cluster policy an interesting tool for economic policy in developing countries. This article offers some theoretical considerations on the use of cluster policy and presents case studies from Saudi Arabia, Morocco, Tunisia, and Algeria.
Keywords: 330; economic development; economic growth; industrial policy; regional policy; development policy; cluster policy; cluster theory; Saudi Arabia; Morocco; Tunisia; Algeria; Industriepolitik; Regionalpolitik; Regionales Cluster; Saudi-Arabien; Entwicklungspolitik; Marokko; Tunesien; Algerien; Algerien